1982
DOI: 10.1136/gut.23.7.608
|View full text |Cite
|
Sign up to set email alerts
|

Male gonadal function in coeliac disease: 1. Sexual dysfunction, infertility, and semen quality

Abstract: 1 in these patients. The aim of the present study was to determine the prevalence of infertility, sexual dysfunction, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 24 publications
1
57
0
1
Order By: Relevance
“…48 In males, impotence, decreased sexual activity, infertility, abnormalities of sperm morphology and motility may be expressions of CD. 49,50 Another presentation of atypical CD is so-called celiac hepatitis, characterized by a gluten-dependent increase in serum transaminases without abnormality of any other liver functions. 51 Both the serum transaminases and mild liver histological damage revert to normal after removal of gluten.…”
Section: Introductionmentioning
confidence: 99%
“…48 In males, impotence, decreased sexual activity, infertility, abnormalities of sperm morphology and motility may be expressions of CD. 49,50 Another presentation of atypical CD is so-called celiac hepatitis, characterized by a gluten-dependent increase in serum transaminases without abnormality of any other liver functions. 51 Both the serum transaminases and mild liver histological damage revert to normal after removal of gluten.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual dysfunction is common without other features of hypogonadism, and improves after gluten withdrawal. Abnormalities of sperm morphology and motility are common in both untreated and treated patients (Farthing et al, 1982). Androgen resistance (Farthing et al, 1983b) and associated hypothalamo-pituitary dysfunction were confirmed after studying 39 men with coeliac disease compared with 19 nutritionally matched but younger males with Crohn's disease.…”
Section: Gastrointestinal Diseasementioning
confidence: 90%
“…Of these, 395 were excluded, and eighteen potentially relevant studies were evaluated. Six studies were excluded because they did not fulfilled elegibility criteria: three studies lacked a control group (5,13,17) , a large population-based study (9) was not designed to compare infertility prevalence in celiac subjects and used U.S. general population as a control group; another study (20) used an inadequate control group (previously known prevalence of silent CD in the northen Sardinian population) and another one (7) assessed the risk of infertility only in male subjects and used Crohn's disease patients as control group. Finally, as shown in Figure 1, twelve studies were included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies do not mention a relationship between CD and certain factors related to male infertility, such as hypogonadism or semen quality deficiencies. Farthing et al (7) described a high frequency of seminal alterations and sexual dysfunction in a cohort of CD male patients compared to Crohn's disease subjects.…”
mentioning
confidence: 99%